Insights Into the Function of the NuA4 Complex in Plants - Espinosa-Cores, Loreto; Bouza-Morcillo, Laura; Barrero-Gil, Javier; Jiménez-Suárez, Verónica; Lázaro, Ana; Piqueras, Raquel; Jarillo, José A.; Piñeiro, Manuel (Frontiers in Plant Science, 2020)
Chromatin remodeling plays a key role in the establishment and maintenance of gene expression patterns essential for plant development and responses to environmental factors. Post-translational modification of histones, including acetylation, is one of the most relevant chromatin remodeling mechanisms that operate in eukaryotic cells. Histone acetylation is an evolutionarily conserved chromatin signature commonly associated with transcriptional activation. Histone acetylation levels are tightly regulated through the antagonistic activity of histone acetyltransferases (HATs) and histone deacetylases (HDACs). In plants, different families of HATs are present, including the MYST family, which comprises homologs of the catalytic subunit of the Nucleosome Acetyltransferase of H4 (NuA4) complex in yeast. This complex mediates acetylation of histones H4, H2A, and H2A.Z, and is involved in transcriptional regulation, heterochromatin silencing, cell cycle progression, and DNA repair in yeast. In Arabidopsis and, other plant species, homologs for most of the yeast NuA4 subunits are present and although the existence of this complex has not been demonstrated yet, compelling evidence supports the notion that this type of HAT complex functions from mosses to angiosperms. Recent proteomic studies show that several Arabidopsis homologs of NuA4 components, including the assembly platform proteins and the catalytic subunit, are associated in vivo with additional members of this complex suggesting that a NuA4-like HAT complex is present in plants. Furthermore, the functional characterization of some Arabidopsis NuA4 subunits has uncovered the involvement of these proteins in the regulation of different plant biological processes. Interestingly, for most of the mutant plants deficient in subunits of this complex characterized so far, conspicuous defects in flowering time are observed, suggesting a role for NuA4 in the control of this plant developmental program. Moreover, the participation of Arabidopsis NuA4 homologs in other developmental processes, such as gametophyte development, as well as in cell proliferation and stress and hormone responses, has also been reported. In this review, we summarize the current state of knowledge on plant putative NuA4 subunits and discuss the latest progress concerning the function of this chromatin modifying complex.